Differential Economic Impacts of Chinese and American Trade Policies on Developed Versus Developing Nations - Dong, Changming (Transactions on Economics, Business and Management Research, 2024)
The trade conflict between the United States and China, the two largest economies in the world, has considerable implications for global economic stability and growth. This topic has been selected due to the necessity of understanding how these trade disputes impact other countries, particularly those heavily dependent on exporting goods to these major economies. The analysis aims to investigate the varied effects of the trade war on both industrialized and developing nations. An analysis is conducted to examine the differential effects of the trade war on industrialized and developing nations by studying the changes in GDP growth rates, unemployment rates, and balance of trade trends. This study examines the distinct economic effects of the China-US trade war on Germany, Canada, and Mexico, which serve as representative examples of developed and developing nations. The results emphasize the significance of customized policy measures to tackle the distinct difficulties and prospects encountered by various economies. Developed countries should prioritize efforts to reduce sluggish economic development and address unemployment in specific sectors. On the other hand, developing nations should take advantage of trade diversion benefits and strengthen their economic resilience. This study enhances the awareness of global trade dynamics and offers vital perspectives for policymakers seeking to negotiate the intricacies of international trade wars.